RANCANG BANGUN ALAT TERMOMETER NON-CONTACT MENGGUNAKAN INFRA RED - Denis Prastio; Fitriap Priyulida (JURNAL MUTIARA ELEKTROMEDIK, 2020)
The purpose of designing this tool is to develop a thermometer that still uses mercury to become a non-contact thermometer using infrared. To use this tool, just turn on the tool and then the infrared sensor is shot at the head of the patient you want to check and the results come out on the display.The method used in this research is experimental by doing system design, testing tools and drawing conclusions. but before doing the design, first prepare a good design of the workpiece in order to get satisfactory results.The results of the measurement on this tool aims to determine the temperature of the human body that we want to check, the test is carried out 6 times, in normal patients the temperature is 36.21 and 36.23, in patients with fever the resulting temperature is 38.14 and 37.18, in patients with hyportemia, temperatures were 35.40 and 35.55.